An Examination of Narratives From Women Offenders: Are Gender-Specific Reentry Efforts Needed? - Koski, Susan V.; Costanza, S. E. (Qualitative Sociology Review, 2015)
In this article, data was gathered from interviews and observations using content and historical analysis of several women from a reentry program in Hartford, CT (n=32). Interviews illustrate that examining a gendered approach of female offenders provides an efficient foundation on which to answer the question of whether reentry programs are truly gender-specific. The needs of women are different than men and therefore there should be a difference in treatment upon reentry. Two main purposes are served: to investigate women’s narratives about the reason for criminal activity and to examine their specific needs for gender-specific reentry programming. The value of qualitative research in life trajectories is emphasized as a tool to understand gender-specific needs with a particular focus on the life course dimensions of entrance, success, and timing (Thornberry 1997).